PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT SUMBER ALFARIA TRIJAYA TBK CABANG CIKOKOL - Intan Nabila; H. Widhi Wicaksono (Journal of Research and Publication Innovation, 2025)
This research aims to test and analyze the population in this research is PT Sumber Alfaria Trijaya Tbk Cikokol branch. The number of observation samples was 32 data obtained using saturated samples. The analysis technique used is multiple linear regression analysis. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The test results show that the independent variables, namely work environment and work discipline, are able to explain the dependent variable, namely employee performance, by 75.8% and the remaining 24.2% is influenced by other factors not included in this research. Multiple linear regression equation Y=11.732-0.018X1+0.574X2. Based on the results of the model feasibility test (F test), it shows that the Fcount value is 45.532 > Ftable 3.330 or the Sig value is 0.000 < 0.05, so Ho3 is rejected and Ha3 is accepted. The test results show that the regression model in this research is suitable for predicting employee performance. Apart from that, it can be concluded that the work environment and work discipline simultaneously affect employee performance at PT Sumber Alfaria Trijaya Tbk Cikokol branch.